Biocompatible graft copolymers from bacterial poly(γ-glutamic acid) and poly(lactic acid). Issue 26 (17th June 2021) - Zaccaria, Cristiana L.; Cedrati, Valeria; Nitti, Andrea; Chiesa, Enrica; Martinez de Ilarduya, Antxon; Garcia-Alvarez, Montserrat; Meli, Massimiliano; Colombo, Giorgio; Pasini, Dario
Abstract : Biocompatible graft copolymers from bacterial poly(γ-glutamic acid) and poly(lactic acid) are realized using a "grafting to" approach combined with click chemistry. Abstract : We report a novel approach for the modular and convergent construction of biocompatible graft copolymers starting from bacterial poly(γ-glutamic acid)(γ-PGA) and incorporating poly(lactic acid) (PLA). This synthesis strategy is controlled at different levels: (a) the choice of a suitable initiator for the ring-opening polymerization of lactide; (b) the chemical elaboration of the polylactic fragments; and (c) their convergent "grafting to" functionalization of bacterial γ-PGA propargyl ester using copper(i )-catalyzed alkyne–azide cycloaddition (CuAAC) click chemistry. The graft copolymers are characterized in terms of their thermal and macromolecular properties, their conformational preferences through molecular modelling, and their cytotoxicity.